Port Congestion Solutions the Future of Efficient Transport Networks in Global Trade - Hicham Samir Belkacem; Omar Idris (Indonesian Maritime Researchers and Lecturers, 2025)
Port congestion has emerged as a critical challenge in global trade, hindering the efficient movement of goods and increasing logistical costs. This research explores the causes of port congestion, its impact on global supply chains, and potential solutions to alleviate these challenges. Through qualitative analysis and case studies, the study examines existing strategies, such as digitalization, better port management practices, and alternative transportation methods. Findings indicate that integrating advanced technologies, including automation and data analytics, could streamline port operations and reduce congestion. Additionally, improving port infrastructure and enhancing intermodal connections between ports and land transportation networks are essential steps towards addressing this issue. The study suggests that a combination of technological innovation and collaborative approaches between stakeholders is necessary to enhance the resilience and efficiency of transport networks in global trade. This research provides valuable insights into the future of port management and its potential to overcome congestion-related challenges, fostering smoother trade flows and boosting economic growth.